Anaerobic performance in skiers tested through analysis of blood lactate concentration - Olmo, H.; Gomez-Lopez, P. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: A high capacity of anaerobic performance is essential to achieve good results in alpine skiing (Bosco et al, 1994; Bacharach, 2003). The test of 30" continuous Jumps (30"Cj) seems to be an effective measurement of this capacity (Andersen et al, 1990; White & Johnson, 1991) although there are other tests to measure it (Raschner et al, 2003). We have compared the values of blood lactate in different physical tests with those obtained in alpine skiing competition.